Features of the Mechanism of Development and Course of Pneumonia Under Exposure to the Organism of Pesticides (Texas Journal of Multidisciplinary Studies, 2022)
The aim of presented work is to study the features of mecha- nism of the development and course of experimental pneumonia against a back- ground of body intoxication by pesticide of OPC - antio group.